2020
DOI: 10.1176/appi.focus.18204
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dose of Selective Serotonin Reuptake Inhibitors, Venlafaxine, and Mirtazapine in Major Depression: A Systematic Review and Dose-Response Meta-Analysis

Abstract: Background Depression is the single largest contributor to non-fatal health loss worldwide. Second-generation antidepressants are the first-line option for pharmacological management of depression. Optimising their use is crucial in reducing the burden of depression; however, debate about their dose dependency and their optimal target dose is ongoing. We have aimed to summarise the currently available best evidence to inform this clinical question. Methods We did a systematic review and dose-response meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
100
3
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(114 citation statements)
references
References 27 publications
7
100
3
4
Order By: Relevance
“…It therefore seems sensible to adjust antidepressant treatment recommendations for both dose and age to optimally meet the needs of individual age-groups. The present reanalysis therefore asked whether antidepressant dosing recommendations reported by Furukawa et al [1] would change in dependence on age.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…It therefore seems sensible to adjust antidepressant treatment recommendations for both dose and age to optimally meet the needs of individual age-groups. The present reanalysis therefore asked whether antidepressant dosing recommendations reported by Furukawa et al [1] would change in dependence on age.…”
Section: Introductionmentioning
confidence: 94%
“…The recent meta-analysis by Furukawa et al [1] reported optimal doses for the use of antidepressants in the acute-phase treatment of adult major depressive disorder (MDD). Results showed a moderate dose-dependent increase in efficacy (response rate) until 40 mg/day fluoxetine equivalents (mg/day FE ) associated with an exponential decrease in tolerability (dropouts due to adverse effects) up to 80 mg/day FE [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations